RECOGNITION AND STATISTICAL SIZE DISTRIBUTION OF MICRODOMAINS IN TEM-IMAGES OF POLYIMIDE FILMS DURING THEIR PROCESSING - Bronnikov, Sergei; Sukhanova, Tatiana (Image Analysis and Stereology, 2011)
The surface morphology of polyamic acid films evolving under heating towards polyimide films is investigated with transmission electron microscopy. Micro-domains observed at the surface of the films are treated statistically and shown to form optimized statistical ensemble(s). The statistical size distribution of the micro-domains is described with the model of reversible aggregation. The distribution parameters, namely the aggregation energy and the mean diameter of micro-domains, are shown to depend on the chemical structure of the polymer and the heating temperature.